2015
DOI: 10.1038/ncomms9486
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz-driven linear electron acceleration

Abstract: The cost, size and availability of electron accelerators are dominated by the achievable accelerating gradient. Conventional high-brightness radio-frequency accelerating structures operate with 30–50 MeV m−1 gradients. Electron accelerators driven with optical or infrared sources have demonstrated accelerating gradients orders of magnitude above that achievable with conventional radio-frequency structures. However, laser-driven wakefield accelerators require intense femtosecond sources and direct laser-driven … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
274
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(298 citation statements)
references
References 37 publications
(53 reference statements)
1
274
2
3
Order By: Relevance
“…ulti-cycle terahertz (THz) pulses with frequencies between 0.1 and 1 THz exhibiting simultaneously high energies (>10 mJ) and peak fields (>100 MV/m) are exciting prospects for transforming nonlinear THz spectroscopy, radar and charged particle acceleration [1] applications. Such a class of sources has the potential to ubiquitize charged-particle accelerator technology and enable unprecedented modalities in biomedical imaging, therapy and protein structure analysis [2].…”
Section: Introductionmentioning
confidence: 99%
“…ulti-cycle terahertz (THz) pulses with frequencies between 0.1 and 1 THz exhibiting simultaneously high energies (>10 mJ) and peak fields (>100 MV/m) are exciting prospects for transforming nonlinear THz spectroscopy, radar and charged particle acceleration [1] applications. Such a class of sources has the potential to ubiquitize charged-particle accelerator technology and enable unprecedented modalities in biomedical imaging, therapy and protein structure analysis [2].…”
Section: Introductionmentioning
confidence: 99%
“…In THz based acceleration a mJ THz laser is longitudinally coupled to a metallic structure loaded with dielectrics [10]. This technique should in principle allow gradients of GV/m but is presently limited by the lack of high power THz sources.…”
Section: Introductionmentioning
confidence: 99%
“…Imai et al 22 used a segmented gallium phosphide (GaP) electro-optic generation crystal to generate a radially polarized terahertz beam with a longitudinal electric field amplitude of 30 V/cm. Nanni et al 4 have also recently reported using a segmented waveplate to convert a linearly polarized terahertz pulse into a radially polarized few-cycle pulse. The use of such time-shifting segmented waveplates is however not applicable to the generation of radially polarized single-cycle pulses.…”
mentioning
confidence: 99%
“…There is a great deal of interest in utilizing the longitudinal electric field component of radially polarized sources for particle acceleration. [1][2][3] Recent demonstrations of acceleration with terahertz radiation within waveguides, with 7 keV acceleration in 3 mm, 4 have increased the interest in high electric field strength terahertz sources. In recent years, magnesium-oxide doped stoichiometric lithium niobate (MgO:SLN) has become a popular non-linear material for use in the generation of linearly polarized terahertz radiation with a high peak electric field strength.…”
mentioning
confidence: 99%